2015
DOI: 10.1002/fes3.52
|View full text |Cite
|
Sign up to set email alerts
|

GplusE: beyond genomic selection

Abstract: GplusE is a strategy for genomic selection in which the accuracy of assessment in the reference population for a primary trait such as yield is increased by the incorporation of data from high‐ throughput field phenotyping platforms. This increase in precision comes from both exploiting genetic relationships between traits and reducing the effect of environmental influences upon them. We describe a collaborative project among researchers and breeders to develop a large reference population of elite UK wheat li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…In our study, we observed that when the training population had at least one full‐sib from a cross, the pedigree‐based predictions performed similar to or gave a maximum increase in accuracy of 0.13 over the genomic prediction accuracies. This implies that although markers account for genomic relationships that occurred among the founders of the population, the narrow variance among full‐sibs and the insignificant contribution of more distant relationships further back in time (before the five generations of pedigree considered), as also observed by Luan et al (2012), might have contributed to high accuracies with the pedigree. In addition, the imperfect estimation of the identity‐by‐state relationships by the limited number of markers available for this study might have resulted in high pedigree‐based prediction accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we observed that when the training population had at least one full‐sib from a cross, the pedigree‐based predictions performed similar to or gave a maximum increase in accuracy of 0.13 over the genomic prediction accuracies. This implies that although markers account for genomic relationships that occurred among the founders of the population, the narrow variance among full‐sibs and the insignificant contribution of more distant relationships further back in time (before the five generations of pedigree considered), as also observed by Luan et al (2012), might have contributed to high accuracies with the pedigree. In addition, the imperfect estimation of the identity‐by‐state relationships by the limited number of markers available for this study might have resulted in high pedigree‐based prediction accuracies.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic methods would enable the sugar and starch profiles of tubers to be more closely examined, whereas high‐throughput imaging will allow plant biomass accumulation to be monitored under various biotic and abiotic stress conditions. The development of high‐throughput phenomic platforms will enable phenotype data to be captured at a rate to match the advances that have occurred with genomic selection (Cobb et al, 2013; Mackay et al, 2015), although there will be a requirement to optimize approaches for individual plant species. In this context, a focus on species‐specific traits for potato, particularly subterranean stolon and tuber characters, will be essential.…”
Section: Increasing the Suite Of Traits That Can Be Evaluated Or Selementioning
confidence: 99%
“…The objective of this study was to explore the effect of level of relatedness between 78 training set and validation set on genomic prediction accuracy using data from a large set of 79 field experiments. To do this, 44 bi-parental or three-way crosses were obtained from four 80 commercial wheat breeders in the United Kingdom, as described for the GplusE Project 81 (Mackay et al, 2015). The crosses had different degrees of relatedness among each other and 82 there were many shared parents.…”
mentioning
confidence: 99%